Moringa oleifera (drumstick tree) seed coagulant protein (MoCP) binds cadmium - preparation and characterization of nanoparticles - Reddy Konada R. S.; Kumar Vinay; Prasad Majeti N. V.; Kumar Nadimpalli S. (The EuroBiotech Journal, 2017)
Moringa oleifera is grown globally. It is a multipurpose tree and the seeds are rich in phytochemicals with antimicrobial activities. The crude powder of seeds clarify the turbid and metal contaminated water. M. oleifera (drumstick tree) seed coagulant protein (MoCP) was isolated to homogeneity from the crude extracts by carboxymethyl cellulose chromatography (CMC) and gel filtration. The molecular weight of the protein on gel filtration was 13 kDa and in SDS-PAGE it migrated as a single band under reducing conditions with molecular mass of 6.5 kDa (dimeric). Immobilized MoCP selectively binds cadmium from aqueous solutions (pH 2.0-7.0) with maximum binding at pH 6.0 in 180 min when tested at 10-600 minutes. It also bound the metal in the concentration range of 30-70mgL-1. The adsorption kinetics was better described by pseudo second order and the data better explained by freundlich isotherm model than Langmuir isotherm model as in Freundlich model the correlation coefficient (R2) is high and the calculated qmax is very close to the experimental qmax rather than Langmuir isotherm model. Furthermore, the nanoparticles of MoCP were prepared and characterized using transmission electron microscopy (TEM). The authenticity of the isolated protein and the nanopraticles prepared was confirmed by specific reactivity with the MoCP antibody raised earlier in our laboratory.